Determining the Fit of a Technology Strategy: An Application of the “Fit As Gestalt” Perspective - Schuh, Guenther; Bachmann, Hedi; Ryschka, Simon (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2016)
Studies have shown that the success of different technology strategies varies with the conditions under which they are derived, e.g. internal or external boundary conditions. Thus, technology strategies fitted to the requirements of an enterprise are a key success factor. Until now, there is little research work done to determine the fit of a technology strategy. Therefore, in our research project, we developed a method to analyse and determine the fit of a technology strategy of an enterprise with its specific internal organizational and strategic context as well as with its external boundary conditions. Prior research on the nterrelationships between technology strategy and influencing factors is mainly focused on single parameters. This article brings an integrated view to the fit of a technology strategy by applying the »fit as gestalts« perspective as well as cybernetic reasoning to the research field of technology strategy.